2016
DOI: 10.1038/ki.2015.308
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution stimulated emission depletion imaging of slit diaphragm proteins in optically cleared kidney tissue

Abstract: The glomerular filtration barrier, consisting of podocyte foot processes with bridging slit diaphragm, glomerular basement membrane, and endothelium, is a key component for renal function. Previously, the subtlest elements of the filtration barrier have only been visualized using electron microscopy. However, electron microscopy is mostly restricted to ultrathin two-dimensional samples, and the possibility to simultaneously visualize multiple different proteins is limited. Therefore, we sought to implement a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 12 publications
6
90
0
Order By: Relevance
“…We have also tested other nephrotic diseases, and they also have podocin staining patterns that correspond to enlarged or effaced foot processes, although not as dramatically as minimal change disease does (data not shown). A recent study using STED to image optically cleared rat kidney tissue also showed similar changes using an experimental model of nephrotic disease, Heymann nephritis [7].…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…We have also tested other nephrotic diseases, and they also have podocin staining patterns that correspond to enlarged or effaced foot processes, although not as dramatically as minimal change disease does (data not shown). A recent study using STED to image optically cleared rat kidney tissue also showed similar changes using an experimental model of nephrotic disease, Heymann nephritis [7].…”
Section: Discussionmentioning
confidence: 66%
“…Adding an extra step to tag podocin for IF does not significantly increase the preparation time for samples. The optical clearing technique used in the recent STED imaging study of rat kidney [7] eliminates the step of tissue sectioning but adds a significant time delay (up to 2 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Helium ion SEM technology has the power to provide superb new insights into the topographical ultrastructure of the glomerulum (Rice et al 2013). Lastly, an improvement of the available clearance techniques might enhance our possibilities to localize proteins in health and disease when combined with high- or super-resolution microscopy (Richardson and Lichtman 2015; Unnersjo-Jess et al 2016). …”
Section: Discussionmentioning
confidence: 99%